Segregated land use sprawl: TOD approach for mixed-use housing development in Kuala Lumpur - Rosni, Nur Aulia; Ponrahono, Zakiah; Mohd Noor, Noorzailawati (Malaysian Institute of Planners, 2018)
Spatial analysis of current land use provides useful insight on urban development trend specifically in measuring sprawl growth. Remote sensing and GIS technologies were applied in this research to measure the phases of segregated urban sprawl growth, focusing on the aspect of mixed land use planning. The findings proved that Kuala Lumpur is currently facing segregated land use sprawl based on the measurement derived from one of LUGI component. This type of sprawl transpired within the residential zone in Kuala Lumpur city, demoting mixed-use development by unravelling different classes of land uses into singleuses, thus promoting high dependency on motorised vehicle and discouraging public and pedestrian modes of transportation. The transit-oriented development is one of necessary approaches to control segregated sprawl and promotes mixed-use development in housing areas within the city.